Tren-tren Pergeseran Pemaknaan Naskh dalam Al-Qur`an : dari Penganuliran ke Penundaan - Wardani, Wardani (Sekolah Tinggi Filsafat Islam Sadra, 2015)
Abstract : This article is aimed to explain trends in Moslem scholarsâ understanding on abrogation (naskh) theory. The naskh has been commonly conceived as final abrogation of particular Quranic verse by other one. But, this term has transformed from naskh as final abrogation to postponement (nasâ). There have been three trends in understanding the naskh as postponement. First, the concept of postponement does not differ basically from the substance of naskh as final abrogation in the sense that both naskh and nas` have same meaning, as the majority of Moslem scholars said. Second, the nasâ has own meaning which differs from the naskh, but both are regarded as complementary to each other, as argued by al-Zarkasyi, al-Biqaâi, and Ibn Asyur. Third, the idea that the postponement constitutes an alternative to the naskh as final abrogation, so its proponents, such as Muhammad âAbduh and Nashr Hamid Abu Zayd rejected the naskh as final abrogation and replaced it by the nasâ as postponement.Keywords : Abrogation (naskh), Postponement (nasâ), Replacement (ibdÄl)Â Abstrak : Artikel ini dimaksudkan untuk menjelaskan tren-tren pemahaman para ulama tentang teori naskh. Naskh umumnya dikonsepsi sebagai penganuliran permanen ayat al-Qurâan tertentu dengan ayat lain. Namun, istilah ini kemudian berkembang dari naskh sebagai penganuliran final menjadi penundaan (nasâ). Ada tiga tren dalam memahami naskh sebagai penundaan. Pertama, konsep penundaan pada dasarnya tidak berbeda dari substansi naskh sebagai penganuliran final dalam pengertian bahwa naskh dan nasâ memiliki makna yang sama, sebagaimana dinyatakan oleh mayoritas ulama. Kedua, nasâ memi-liki maknanya sendiri yang berbeda dengan naskh, tapi kedua dianggap saling melengkapi, sebagai-mana ditegaskan oleh al-Zarkasyi, al-Biqaâi, dan Ibn Asyur. Ketiga, ide tentang penundaan merupakan sebuah alternatif terhadap naskh sebagai penganuliran final, sehingga para pendukungnya, semisal Muhammad âAbduh dan Nashr Hamid Abu Zayd menolak naskh sebagai penganuliran final dan meng-gantinya dengan nasâ sebagai penundaan.Kata-kata kunci : Penganuliran (naskh), Penundaan (nasâ), Penggantian (ibdÄl)